2014
DOI: 10.1080/13887890.2014.963712
|View full text |Cite
|
Sign up to set email alerts
|

Does the damming of streams in the southern Amazon basin affect dragonfly and damselfly assemblages (Odonata: Insecta)? A preliminary study

Abstract: Our goal was to investigate whether the loss of riparian forests alters the structure of assemblages and populations of dragonflies and damselflies. We tested the hypothesis that the composition of the odonate assemblages found upstream from dams are significantly different from those found downstream of these barriers. To test the hypothesis, we investigated stream sectors upstream and downstream of three dams located at the extreme of the southern Amazon basin, in the Brazilian state of Mato Grosso. We colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
3
12
0
Order By: Relevance
“…Assessing biodiversity is one of the greatest challenges for scientists, especially in regions of high variation, such as the Tropical region [ 36 ]. The methodology applied in the present study proved to be efficient, and the richness assessed was similar to what was found in studies at the regional and local scale [ 6 , 17 , 30 , 42 , 43 ]. We observed variation in species richness patterns, especially regarding sampling time, evidencing noon was the best time to sample dragonflies.…”
Section: Discussionsupporting
confidence: 76%
“…Assessing biodiversity is one of the greatest challenges for scientists, especially in regions of high variation, such as the Tropical region [ 36 ]. The methodology applied in the present study proved to be efficient, and the richness assessed was similar to what was found in studies at the regional and local scale [ 6 , 17 , 30 , 42 , 43 ]. We observed variation in species richness patterns, especially regarding sampling time, evidencing noon was the best time to sample dragonflies.…”
Section: Discussionsupporting
confidence: 76%
“…The HII has proven to be a valuable descriptor of the environmental integrity of Amazonian streams, and when applied to odonate fauna, it has also been shown to be a good predictor of the abundance of individuals and the species richness and composition of these communities (Brasil, Batista, et al., ; Brasil, Giehl, et al., ; Carvalho, Pinto, Oliveira‐Júnior, & Juen, ; Juen, Oliveira‐junior, & Shimano, ; Monteiro‐Júnior, Couceiro, Hamada, & Juen, ; Monteiro‐Júnior et al., ; Oliveira‐Junior et al., ). Major alterations, principally in species composition, tend to be observed at streams with integrity values of <0.6 or 0.7.…”
Section: Methodsmentioning
confidence: 99%
“…Our results indicate that turnover is the most important component of the variation in beta diversity in the Zygoptera communities of Amazonian streams, confirming the predictions of our first hypothesis. Local (alpha) species richness was relatively low in comparison with previous studies using similar sampling effort in streams of the Brazilian Atlantic Forest (Silva et al ., ), Cerrado Savanna (Júnior et al ., ; Carvalho et al ., ; Dutra & De Marco, ) and the Amazon‐Cerrado transition zone (Brasil et al ., ,; Juen et al ., ). The Amazon region, however, has one of the highest levels of alpha diversity found anywhere on the planet in a number of different taxonomic groups (Vinet & Zhedanov, ), including the Odonata (Kalkman et al ., ), which may be related to the large number of endemic species found in the different biogeographic regions (Juen & De Marco, ).…”
Section: Discussionmentioning
confidence: 99%
“…In each stream, we demarcated a linear transect of 100 m, and captured all the adult Zygoptera specimens observed along the transect, with a mean sampling period of 1 h, using an entomological hand-net of 40 cm in diameter and 65 cm in length. To minimise bias related to the different types of thermoregulation (thermal conformers, heliotherms and endotherms: May, 1976), we collected specimens only on sunny days between 10:00 a.m. and 2:00 p.m., when the sun's rays reach the principal channel of the streams Brasil et al, 2014b;Miguel et al, 2017a).…”
Section: Biotic Variablesmentioning
confidence: 99%